Grabbing aid for disabled users and users with long nails / Loo Jian Chuan and Chin Alicia - Loo Jian, Chuan; Chin, Alicia (2022)
The paper presents the development of an innovative idea to design a grabbing aid for disabled users and users with long nails. The paper consists of the process gone through in making the grabbing aid, as well as the designs created for the grabbing aid.